The Effect of Entrepreneurial Self-Efficacy on Turnover Intention: Mediated by Entrepreneurial Intention and Moderated by Quality of Work Life - Unwan Falahy; Alim Setiawan Slamet; Arry Ekananta (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of enactive mastery experience on entrepreneurial self-efficacy and its implications for entrepreneurial intention and turnover intention in startup businesses. The results indicate that enactive mastery experience has a positive and significant effect on entrepreneurial self-efficacy. The more experience an employee has in entrepreneurial values, the stronger their confidence in their entrepreneurial abilities. Furthermore, entrepreneurial self-efficacy was found to positively influence both entrepreneurial intention and turnover intention to startup businesses. This means that employees with higher self-confidence in entrepreneurship are more likely to intend to leave their current job to start their own business. The study also confirms that entrepreneurial intention mediates the relationship between entrepreneurial self-efficacy and turnover intention. Additionally, the quality of work life significantly moderates the relationship between entrepreneurial intention and turnover intention, where a high quality of work life can reduce the tendency of employees to leave their jobs despite having entrepreneurial intentions. These findings provide important insights for organizational management in understanding the dynamics of employees’ entrepreneurial intentions and developing talent retention strategies.